Microbial dynamics in the ripening process of Vorarlberger Alpkäse: farm-specific variations at two Austrian alpine farms - Künz, Johannes Josef; Roch, Franz-Ferdinand; Dzieciol, Monika; Sofka, Dmijtri; Hilbert, Friederike; Selberherr, Evelyne (Frontiers in Microbiology, 2025)
IntroductionVorarlberger Alpkäse (VA) is a Protected Designation of Origin (PDO) Austrian heritage cheese produced from raw milk during the summer grazing period in the Alps. In addition to conducting clinical examinations of cows whose raw milk is used for VA cheese production, this study investigates the microbiota of raw milk and cheese from two alpine farms.MethodsRaw milk, curd, and cheese core samples were collected and analysed using qPCR and 16S rRNA gene amplicon sequencing to determine bacterial loads and the microbial community composition.ResultsThe microbial community in raw milk showed significant variation in alpha diversity and taxonomy during the alpine sojourn, with Pseudomonas, Staphylococcus, Paenibacillus and Lactobacillus being dominant. The cheese curd microbiota was initially diverse, with Pseudomonas, Acinetobacter, the Shigella complex, Lactobacillus and Hafnia-Obesumbacterium being most abundant. During ripening, Lactobacillus became the predominant genus, while the overall diversity decreased.DiscussionDifferences in microbial communities were observed between the two farms, likely due to variations in production conditions and domestic microbiota. These findings highlight the impact of alpine farming practices on the raw milk and cheese microbiota, influencing the unique characteristics of VA.